Pelaksanaan Pembelajaran Program Khusus Bina Gerak Untuk Anak Cerebral Palsy Pada Masa Pandemi Covid-19 - Novira, Nadia; Nurhastuti, Nurhastuti (Jurnal Penelitian Pendidikan Khusus, 2021)
This study aims to find out the implementation of special program learning for children with cerebral palsy during the covid-19 pandemic. The research method used is descriptive with a qualitative approach. The subjects in the study were class X teachers, principals, and parents of cerebral palsy students. The data collection techniques are carried out through observation, interview, and documentation studies which are then analyzed, presented, and drawn conclusions.  The results of the study are learning special programs built in motion during the covid-19 pandemic carried out online. Motion-specific program learning materials are provided based on the characteristics and needs of cerebral palsy students.  Obstacles in the learning of special programs are the mood of students who are easily changed and supporting media for the implementation of limited learning. The efforts made are to make a study visit to the student's home once a month, provide motivation, and lend the learning media needed by students.